Interactions between cranberries and fungi: the proposed function of organic acids in virulence suppression of fruit rot fungi - Tadych, Mariusz; Vorsa, Nicholi; Wang, Yifei; Bergen, Marshall S.; Johnson-Cicalese, Jennifer; Polashock, James J.; White, James F. (Frontiers in Microbiology, 2015)
Cranberry fruit are a rich source of bioactive compounds that may function as constitutive or inducible barriers against rot-inducing fungi. The content and composition of these compounds change as the season progresses. Several necrotrophic fungi cause cranberry fruit rot disease complex. These fungi remain mostly asymptomatic until the fruit begins to mature in late August. Temporal fluctuations and quantitative differences in selected organic acid profiles between fruit of six cranberry genotypes during the growing season were observed. The concentration of benzoic acid in fruit increased while quinic acid decreased throughout fruit development. In general, more rot-resistant genotypes showed higher levels of benzoic acid early in fruit development and more gradual decline in quinic acid levels than that observed in the more rot-susceptible genotypes. We evaluated antifungal activities of selected cranberry constituents and found that most bioactive compounds either had no effects or stimulated growth or reactive oxygen species (ROS) secretion of four tested cranberry fruit rot fungi, while benzoic acid and quinic acid reduced growth and suppressed secretion of ROS by these fungi. We propose that variation in the levels of ROS suppressive compounds, such as benzoic and quinic acids, may influence virulence by the fruit rot fungi. Selection for crops that maintain high levels of virulence suppressive compounds could yield new disease resistant varieties. This could represent a new strategy for control of disease caused by necrotrophic pathogens that exhibit a latent or endophytic phase.